Hypertension in obstructive sleep apnea : the hidden role of renin–angiotensin–aldosterone system dysregulation - Loh, Huai Heng; Tay, Siow Phing; Koa, Ai Jiun; Yong, Mei Ching; Asri, Said; Chai, Chee Shee; Natasya Marliana, Abdul Malik; Anselm Su, Ting; Bonnie Tang, Bao Chee; Florence Tan, Hui Sieng; Elena Aisha, Azizan; Norlela, Sukor (BioMed Central Ltd, 2025)
Background